Effects of Passive Leadership in the Digital Age - Wang, Cheng-Hui; Liu, Gloria H. W.; Lee, Neil Chueh-An (Frontiers in Psychology, 2021)
Organizations must adapt to the trend of digitalization. Nowadays, social media engagement editors play an increasingly crucial role for organizational growth and prosperity in the digital age. Engagement editors are usually tasked to perform the functions of marketing, content production, and data analysis. They have to manage online communities on behalf of the organization, and encounter online audiences' frequent toxic and aggressive behaviors. Engagement editors thus are prone to emotional stress. Substantial literature has examined the influence of leadership style on employee performance. However, passive leadership is rarely studied. This research investigates (1) whether passive leadership would negatively affect engagement editors' performance (i.e., online interaction with audiences); and (2) how the negativity would be ameliorated by certain organizational policies (i.e., job autonomy) and their individual attributes (i.e., employee resilience) from the conservation of resource perspective. We surveyed 122 engagement editors and used the smartPLS 3.2.9 to analyze the data. This research provides important theoretical and practical implications.